1995
DOI: 10.1097/00004032-199508000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure in Pediatric Cardiac Catheterization

Abstract: Radiation doses to staff involved with pediatric cardiac catheterization were measured using thermoluminescent dosimeters in 18 procedures. The average doses to the lens and thyroid, and the effective dose per procedure to the main operating physicians was 88, 180, and 8 microSv, respectively; to assistant physicians, 23, 51, and 2 microSv; and to technicians, 23, 27, and 2 microSv. In some procedures, the dose to the technician's hand approached 1,500 microSv. The doses received by physicians were proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Carinou et al (2015) recently provided a comprehensive review of literature pertaining to the relationship between eye lens dose and externally monitored exposure. Several prior studies reported externally monitored dose to eye lens dose conversion factors in the range 0.44-0.87 for interventional cardiology and/or radiology procedures (Janssen et al 1992, Li et al 1995, Vañó et al 1998, Kicken et al 1999, Covens et al 2007, Lie et al 2008, Sánchez et al 2016. The current work compares favorably with this prior work, with percent LCD values for the left eye in the range 59%-72% and for the right eye in the range 22%-27%.…”
Section: Discussionmentioning
confidence: 59%
“…Carinou et al (2015) recently provided a comprehensive review of literature pertaining to the relationship between eye lens dose and externally monitored exposure. Several prior studies reported externally monitored dose to eye lens dose conversion factors in the range 0.44-0.87 for interventional cardiology and/or radiology procedures (Janssen et al 1992, Li et al 1995, Vañó et al 1998, Kicken et al 1999, Covens et al 2007, Lie et al 2008, Sánchez et al 2016. The current work compares favorably with this prior work, with percent LCD values for the left eye in the range 59%-72% and for the right eye in the range 22%-27%.…”
Section: Discussionmentioning
confidence: 59%
“…Radiation protection for medical personnel is the standard of care for procedures involving ionizing radiation, and this topic has been extensively investigated 9–21 . Although there has been a decrease in the occupational radiation dose for most medical workers, the areas of cardiovascular and interventional radiology appear to be exceptions 1 , 9 .…”
Section: Discussionmentioning
confidence: 99%